A new species and phylogenetic insights in Hesiospina (Annelida, Hesionidae) - Bonifácio, Paulo; Lelièvre, Yann; Omnes, Emmanuelle (Zootaxa, 2018)
Hesionids are a very speciose group of polychaetes. In the deep sea, they occur in different environments such as hydrothermal vents, cold seeps, abyssal depths or whale falls. In the present study, a new species of Hesionidae, Hesiospina legendrei sp. nov. has been identified based on morphological and molecular (16S and COI genes) data from hydrothermal vents located in Juan de Fuca Ridge (NE Pacific Ocean). This new species is characterized by trapezoid prostomium; proboscis with high number of distal papillae (20–27), a pair of sac-like structures inserted ventro-laterally in proboscis; notopodia lobe reduced with multiple, slender aciculae on segments 1–5; and neuropodia developed with single, simple chaeta, and numerous, heterogomph falcigers, with 1–2 inferiormost having elongated hood. Hesiospina legendrei sp. nov. is the third described species in the genus. Sequences from the two previously described Hesiospina species are included in the molecular analyses, and although the genes used in this study are not sufficient to resolve the relationships on genus level, the result raises questions about the cosmopolitan aspect of H. vestimentifera.